2010
DOI: 10.1007/s11250-010-9727-7
|View full text |Cite
|
Sign up to set email alerts
|

Anthelminthic activity of acetone extract and fractions of Vernonia amygdalina against Haemonchus contortus eggs and larvae

Abstract: The current control of parasitic nematodes in small ruminants relies on the use of chemical anthelminthics, but the development of resistance and the problem of drug residues require research into alternatives. Acetone extract and solvent-solvent fractions of Vernonia amygdalina Del. (Compositae) were evaluated in vitro for potential anti-parasitic effects against the eggs and larvae of Haemonchus contortus. Significant effects were obtained with the extract and fractions but differences were observed dependin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 18 publications
1
28
0
1
Order By: Relevance
“…A study by Molgaard et al (2001), using water extract of leaves, stem, root and root bark of V. amygdalina were able to kill cestodes of Hymenolepis diminuta after 24 hours of treatment. A recent study by Ademola and Eloff (2011), revealed a significant effects on different development stages of Haemonchus contortus that varied with solvent used for extraction of active ingredient.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Molgaard et al (2001), using water extract of leaves, stem, root and root bark of V. amygdalina were able to kill cestodes of Hymenolepis diminuta after 24 hours of treatment. A recent study by Ademola and Eloff (2011), revealed a significant effects on different development stages of Haemonchus contortus that varied with solvent used for extraction of active ingredient.…”
Section: Discussionmentioning
confidence: 99%
“…Results showed that LAE has an ovicidal effect with doses of 250 and 500 µg/mL, which may be due to the condensed tannins in L. acapulcensis (116.3 g/kg DM; Table 1). Ademola and Eloff (2011), in their study with Vernonia amygadalina acetone extracts, inhibited egg hatching and larval Olmedo-Juárez et al Gea et al, 2011). Thus possible anthelmintic effects of tanniniferous plants may depend on their CT contents as well as on other CT parameters such as the monomeric composition and degree of polymerisation (i.e., average size of tannin molecules).…”
Section: Eggs Hatch and Larval Development Assaymentioning
confidence: 95%
“…The roots of V. amygdalina have been used for gingivitis and toothache due to its proven antimicrobial activity from the previous work being done on it [2]. In North America, of the 17 species of Vernonia all have the same effective properties as a blood purifier, uterus toner and helps also in the prevention of atherosclerosis [22,41].…”
Section: Introductionmentioning
confidence: 99%